Using Local Drama in Writing and Speaking: EFL Learners’ Creative Expression - Dwi Astuti Wahyu Nurhayati (Yayasan Visi Intan Permata, 2016)
Creating encouragement among students to speak up and to write is not easy. It is seen on their responses of joining speaking and writing class; most students suppose that speaking and writing English are difficult especially to utter and organize their ideas freely. Problems of speaking include inhibition, nothing to say, low participation, mother-tongue use; writing problems include they lack ideas, organizing of ideas, rhetoric or pattern of thought, cohesion and coherence. However to cope with these problems, this study offers the variation performance in delivering ideas or activities through writing a script and conducting a drama. The steps of learning writing are (1) Creative Expression (responding to the ideas that learners produce; (2) Composing Process: planning-writing-reviewing framework using dramatic structure: orientation, complication, sequence of events, resolution and coda; (3) Genre and context of writing (Building Knowledge of Field (BKoF), Modeling of Text (MoT), Joint Construction of Text (JCoT), and Independent Construction of Text (ICoT and Local Drama as their creative expression: Learners use pattern they have developed to write a script). In speaking, before conducting the performance the students are divided into some groups to create the learning community, the steps are: create script based on themes, next consult the script (discuss their creative expreesion), observe the characters play, their characterization, mime, and other aspects, practice the script, and finally perform drama outdoor. As the result they become more self-confidence to utter ideas, expressive including writing a script, drama is considered as an appealing learning strategy which promotes not only goal-oriented learning but also emotional intelligence skills.Key words: teaching, writing and speaking, drama